A Study into Metaphors in American and Vietnamese Declaration of Independence - Nguyen Thi Thanh Huyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This study aimed to describe the similarities and differences between American and Vietnamese declarations of independence regarding the use of metaphors. The method was to analyze metaphors in the two corpora separately as well as comparatively. It is argued in this study that both corpora use metaphors as a rhetorical device to serve political purposes, namely, reinforcing the strength of indictment and denunciation of the oppressive rulers, portraying the citizens’ sufferings and encouraging them to support their new government. It is further revealed that metaphors of spiritual beliefs seemed to dominate in the American corpus, which might be explained by the unique historical American feature, while in the Vietnamese one, such kind of metaphor was not found. Received 2nd February 2018; Revised 15th June 2018; Accepted 20th October 2018